Bond Pricing and the Term Structure of Interest Rates: A New Methodology for Contingent Claims Valuation - Heath, David; Jarrow, Robert; Morton, Andrew (Econometrica, 1992)
David Heath, Robert Jarrow, Andrew Morton, Bond Pricing and the Term Structure of Interest Rates: A New Methodology for Contingent Claims Valuation, Econometrica, Vol. 60, No. 1 (Jan., 1992), pp. 77-105